2008
DOI: 10.1177/1533210108317232
|View full text |Cite
|
Sign up to set email alerts
|

Safe Effective Nondrug Treatment of Chronic Depression: A Review of Research on Low-Voltage Cranial Electrical Stimulation and Other Adjunctive Therapies

Abstract: Although clinical practice guidelines tend to emphasize pharmacological treatments for chronic depression, safe and effective nondrug treatments are available. This article reviews three decades of research at the Shealy Institute on nonpharmacological treatments for chronic depression in chronic pain patients via low-voltage electrical stimulation and other adjunctive therapies. More than 30,000 chronically depressed patients have been treated with cranial electrical stimulation at 1 to 2 mA at 15,000 Hz, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The CES treatment was delivered by two electrodes covered with damp sponges and placed over the temples bilaterally with 2 mA of alternating current for one 20-minute session per day for the active treatment group. The use of 2 mA current was recommended by the manufacturer and has been used in other studies evaluating CES treatment effects ( Shealy and Thomlinson, 2008 ). The sham CES treatment was performed by a trained technician who did not take part in any other aspect of the study, by turning the current on until the patient experienced a tingling sensation on the scalp, then turning it off.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CES treatment was delivered by two electrodes covered with damp sponges and placed over the temples bilaterally with 2 mA of alternating current for one 20-minute session per day for the active treatment group. The use of 2 mA current was recommended by the manufacturer and has been used in other studies evaluating CES treatment effects ( Shealy and Thomlinson, 2008 ). The sham CES treatment was performed by a trained technician who did not take part in any other aspect of the study, by turning the current on until the patient experienced a tingling sensation on the scalp, then turning it off.…”
Section: Methodsmentioning
confidence: 99%
“…A review of CES treatments over the last 30 years done by Shealy and Thomlinson (2008) showed that out of approximately 30,000 patients with chronic pain who also had symptoms of depression, about 50% showed clinical improvement of depressive symptoms when treated with CES with 1–2 mA, with minimal side effects. However, many of these were uncontrolled, open-label studies and allowed unwitnessed patient self-treatment at home ( Shealy and Thomlinson, 2008 ).…”
mentioning
confidence: 99%